2016
DOI: 10.2500/ar.2016.7.0167
|View full text |Cite
|
Sign up to set email alerts
|

Transorbital Endoscopic Identification of Supernumerary Ethmoid Arteries

Abstract: Background:Anterior and posterior ethmoid arteries supply the paranasal sinuses, septum, and lateral nasal wall. Precise identification of these arteries is important during anterior skull base procedures, endoscopic sinus surgery, and ligation of ethmoid arteries for epistaxis refractory to standard treatment. There is controversy in the literature regarding the prevalence of supernumerary ethmoid arteries.Objective:This study examined the prevalence of supernumerary ethmoid arteries by using direct visualiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
0
6
0
8
Order By: Relevance
“…The previously reported finding of accessory foramen in North American Caucasians (35%) is higher than in our Icelandic cohort. One study reported a 42% bilateral prevalence in an ethnically heterogeneous group . Because these nonmatching data sets were extracted from studies analyzing different ethnic groups, a direct comparison cannot be made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previously reported finding of accessory foramen in North American Caucasians (35%) is higher than in our Icelandic cohort. One study reported a 42% bilateral prevalence in an ethnically heterogeneous group . Because these nonmatching data sets were extracted from studies analyzing different ethnic groups, a direct comparison cannot be made.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent anatomic studies have suggested that up to 6 branches can be present within a single orbit. A number of studies have described osteometric quantification of the ethmoid foramina as a surrogate for the number of actual ethmoidal arteries, with most studies analyzing heterogeneous ethnic cohorts. However, established ethnic differences in orbital morphology suggest that there may be concomitant significant differences in the presence and symmetry of supernumerary ethmoidal vessels across patient groups.…”
mentioning
confidence: 99%
“…The classic teaching is that the anterior ethmoid artery located 24 mm posterior to the anterior lacrimal crest and the posterior ethmoid artery located 12 mm further posterior and 6 mm from the optic canal. In reality, the ethmoid arterial system is variable in number and location of its branches, most often with 3 arteries in unpredictable positions, 10 but can be visualized on CT. Other important structures in the medial orbit are the medial rectus muscle, the medial canthal tendon, the trochlea, and the nasolacrimal sac.…”
Section: Anatomymentioning
confidence: 99%
“…The authors refer to it in different terms, such as supernumerary, tertiary, intermediate, accessory, or middle ethmoidal artery. 1,2 The European position paper on the anatomical terminology of the internal nose and paranasal sinuses suggests the term of accessory ethmoidal artery (AcEA) and it refers a prevalence of 40% according to the Lang J's study. 3,4 However, neither the international anatomical terminology nor the classical anatomy books make reference to AcEA, [5][6][7][8] which creates serious doubts about its existence and if so about its true anatomical origin.…”
Section: Introductionmentioning
confidence: 99%
“…These arteries are responsible for the nose bleeding in approximately 20% of cases. 1,2 Exceptional intractable epistaxis can involve other different arteries. These reports mention posterior ethmoidal artery, the palatovaginal artery, or branches from facial artery as possible causes.…”
Section: Introductionmentioning
confidence: 99%